Two new species of the genus Stenohya Beier, 1967 (Pseudoscorpiones, Neobisiidae) from China - Zhao, Yong-Wei; Zhang, Feng; Jia, Ying (Zootaxa, 2011)
Two new species of the genus Stenohya are described from China: Stenohya curvata sp. nov. from Yunnan Province and S. xiningensis sp. nov. from Qinghai Province, China. Detailed diagnosis, descriptions and illustrations of the two new species are presented.